The Paradox of Social Media: The De-democratization of Malaysia - Leo Agustino; Badrul Azmier Mohamed (Jurnal Administrasi Publik, 2015)
Today, social media is perceived as “the media.” Blogs and bloggers have changed journalism; YouTube has discovered rare and raw talents; and “the trinity” (Facebook, Twitter, YouTube) have sparked revolutions. Focusing on end-users instead of producers and its interactive-ness are two paramount characters that permit ordinary people to engage in extra-ordinary activities. From the showbiz to politics, social media has left its marks. The World political events in recent years, in particular Arab Spring of MENA (Middle East and North Africa) have showcased positive link between social media and democratization. Malaysia has experienced quite a similar phenomenon to MENA in the verge of the 12th General Election (GE-12), held on March 8, 2008. The failure of the only ruling coalition, Barisan Nasional (National Front, or BN) to retain its two-third majority in the GE-12 is an empirical evident of people’s desire and aspiration for free and fair elections, good-governance, and democratization which are very different from race-based politics. At a glimpse, the results of the 13th General Election (GE-13) which was held on May 5, 2013 are quite similar to the GE-12. Yet, deeper analyses indicated race-base politics and “strong government” has made a comeback. Hence, this article explores the paradox when the state is not only interfering but also participating in social media. This exploration demonstrates social media is not only meant for the masses; and that by possessing money, machinery, and authority; the state is potentially dominant at social media.